Hexes of the deadwood forest - Szpila, Agnieszka (Pantheon Books, 2026)
"An explosive, jaw-dropping debut about a woman who loses her job as an oil company CEO after she's filmed having sex with a tree in her sleep, a calamity that unravels her mind, spiraling her through history until she's united with a centuries-old coven of ecstatically revolutionary women"-- Provided by publisher.